Transfer of Intravenous Remimazolam into Milk of Lactating Sheep and Uptake by Breast-fed Lambs - Schmalix, Wolfgang; Onyuro, Maureen; Pesic, Marija; Karl-Uwe-Petersen; Stoehr, Thomas (Current Drug Metabolism, 2025)
IntroductionRemimazolam is a short-acting sedative/anesthetic. For safe breastfeeding, information on the extent and possible risks of remimazolam being passed over to the infant through mother´s milk is needed. The objective of this work was to study the transfer of remimazolam from maternal to infant circulation by mother´s milk in an animal model.MethodsThree lactating British milk sheep received intravenous remimazolam (0.4 mg/kg bolus plus 4-hr-infusion at 1 or 2 mg/kg/hour). Drug profiles were recorded in plasma and milk. Six suckling lambs were administered remimazolam by intravenous and oral gavage administration for a comparison of plasma concentration profiles of remimazolam and its primary metabolite, CNS7054.ResultsTreatment of lactating sheep induced dose-dependent sedation and loss of consciousness. At the end of infusion, the concentration of remimazolam was higher in milk than in plasma. The subsequent elimination of remimazolam from milk was rapid, although somewhat slower than from plasma.DiscussionIn lambs, intravenous, but not oral, remimazolam (2 mg) caused different grades of sedation/anesthesia (fully reversible within 8 to 15 min). Mean plasma Cmax was 278.3 ng/mL after intravenous and 1.3 ng/mL after oral administration. Oral gavage resulted in a sizable plasma concentration of CNS7054 (Cmax around 100 ng/mL), indicating efficient intestinal absorption of the parent drug, followed by extensive first-pass metabolic elimination, leading to negligible bioavailability of oral remimazolam.ConclusionIn mother´s milk, remimazolam reaches higher concentrations than in plasma and is cleared by redistribution to the central compartment for final hepatic elimination. In lambs, oral remimazolam results in minimal plasma concentrations, suggesting that safety concerns regarding breast-fed infants would be minor and could be completely alleviated by a short nursing interruption.
Keywords: remimazolam